Plasmodesmata-Involved Battle Against Pathogens and Potential Strategies for Strengthening Hosts - Liu, Jie; Zhang, Lin; Yan, Dawei (Frontiers in Plant Science, 2021)
Plasmodesmata (PD) are membrane-lined pores connecting adjacent cells to mediate symplastic communication in plants. These intercellular channels allow cell-to-cell trafficking of various molecules essential for plant development and stress responses, but they can also be utilized by pathogens facilitating infection. Some pathogens or their effectors are able to spread through PD by modifying their permeability. On the other hand, plants developed various corresponding defense mechanisms including the regulation of plasmodesmata to impede pathogen spreading. In this review, we aim to illuminate the roles of PD in the interactions between pathogens and plants during infection. We summarize the PD-involved pathogenic infections and the modification of PD by pathogens and hosts. Furthermore, we propose several hypothesized strategies for enhancing the disease resistance of hosts by appropriate modulation of callose deposition and plasmodesmal permeability based on current knowledge.